2015
DOI: 10.4049/jimmunol.1402256
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD69 Interference with Sphingosine-1-Phosphate Receptor Function Regulates Peripheral T Cell Retention

Abstract: Tissue-resident memory T cells provide local immune protection in barrier tissues, such as skin and mucosa. However, the molecular mechanisms controlling effector T cell retention and subsequent memory formation in those locations are not fully understood. In this study, we analyzed the role of CD69, an early leukocyte activation marker, in regulating effector T cell egress from peripheral tissues. We provide evidence that CD69 surface expression by skin-infiltrating CD8 T cells can be regulated at multiple le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
407
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(426 citation statements)
references
References 25 publications
19
407
0
Order By: Relevance
“…Although CD69 is an early T-cell activation marker, it is also considered a hallmark of memory CD8 αβ T-cell residency, which functions by inhibiting the expression of S1PR1 (19). Surprisingly, we found that even though γδ Trm cells express CD69, they also express S1P receptors 1 and 4 as confirmed by RT-PCR (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 46%
“…Although CD69 is an early T-cell activation marker, it is also considered a hallmark of memory CD8 αβ T-cell residency, which functions by inhibiting the expression of S1PR1 (19). Surprisingly, we found that even though γδ Trm cells express CD69, they also express S1P receptors 1 and 4 as confirmed by RT-PCR (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 46%
“…The a E b 7 integrin CD103 promotes cell adherence to E-cadherin expressed on tissue epithelial cells (47), whereas C-type lectin CD69 inhibits sphingosine-1-phosphate receptor 1, leading to tissue retention (48,49). In this study, we identified influenza-specific lung memory T cells expressing CD103 and CD69 in rhesus monkeys.…”
Section: Discussionmentioning
confidence: 84%
“…34 CD69 promotes the early retention of CD8 + T cells in the skin before the expression of Klf2 and S1pr1 are efficiently suppressed. 44 Mechanistically, CD69 inhibits the function of S1pr1 and blocks the egress of T cells. 45 Even though the down-regulation of Klf2 and S1pr1 is a common signature of T RM , 46 the rapid induction of CD69 helps to retain T RM precursors when there is residual activity of S1pr1 at early stages of T RM differentiation.…”
Section: Tissue Specific Features Of Trm Cellsmentioning
confidence: 99%
“…46,75,88 Mechanistically, PI3K/Akt pathway is activated by cytokine signals to inhibit the expression of transcription factor Foxo1 and therefore enforce the down-regulation of K1f2 46 Various combinations of pro-inflammatory cytokines can suppress the expression of Klf2 in activated CD8 + T cells in vitro, including type I IFN, IL-12 and IL-18. 46,88 However, type I IFN does not significantly alter T RM differentiation 44 and IL-12 inhibits early differentiation and promotes long-term maintenance of gut T RM . 89 Thus, the function of different cytokines in T RM cells will require further clarification in different tissues under various inflammatory conditions in vivo.…”
Section: Transcriptional Regulation Of Trm Cellsmentioning
confidence: 99%